2022
DOI: 10.3390/catal12101154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen-Donor of Heavy Crude Oil Catalytic Aquathermolysis in the Presence of a Nickel-Based Catalyst

Abstract: The transformations of oil components from the Zyuzeevskoye field during catalytic aquathermolysis in the presence of a nickel-containing catalyst precursor and hydrogen donors were studied. It was found that the yield of gasoline and diesel fractions increased by more than 36% in the case of catalytic aquathermolysis in the presence of tetralin. The maximum conversion of asphaltenes was achieved with a simultaneous slowing down of coke formation by four times. The calculation of the structural-group parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The experimental results show that the addition of cyclohexane modification increases the oil amount. Urazov et al [88] . studied the transformation of crude oil components during catalytic hydrothermal cracking in the presence of nickel‐containing catalyst precursors and tetralin as hydrogen donor.…”
Section: Hydrogen Storage Properties and Sulfur Tolerance Of Aromatic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results show that the addition of cyclohexane modification increases the oil amount. Urazov et al [88] . studied the transformation of crude oil components during catalytic hydrothermal cracking in the presence of nickel‐containing catalyst precursors and tetralin as hydrogen donor.…”
Section: Hydrogen Storage Properties and Sulfur Tolerance Of Aromatic...mentioning
confidence: 99%
“…The experimental results show that the addition of cyclohexane modification increases the oil amount. Urazov et al [88] studied the transformation of crude oil components during catalytic hydrothermal cracking in the presence of nickel-containing catalyst precursors and tetralin as hydrogen donor. It was found that the yield of gasoline and diesel fractions increased by more than 36 % when the hydrothermal cleavage was catalyzed in the presence of tetralin.…”
Section: Hydrogen Storage Propertiesmentioning
confidence: 99%
“…Ramos et al observed a 22.7% increase in the content of aromatics using Co/MoS 2 nanocatalysts under specific conditions . Other studies also reported a significant improvement in the quality of heavy crude combining various catalysts and experimental reaction conditions. …”
Section: Introductionmentioning
confidence: 99%
“…The synergistic mechanism between nanoparticles and surfactants can address foam-related issues in oil displacement applications. Metal nanocrystal catalysts can be highly dispersed in heavy oil and promote desulfurization and chain scission reactions of heavy oil macromolecules by significantly increasing the specific surface area and providing a large number of active sites, thereby reducing the viscosity of heavy oil and improving recovery rate [12][13][14]. Hendraningrat and other researchers [15] conducted a series of studies on nanofluid displacement by varying parameters such as rock core permeability, rock wettability, and nanofluid concentration.…”
Section: Introductionmentioning
confidence: 99%